Preserved pharmacokinetic exposure and distinct glycemic effects of insulin degludec and liraglutide in IDegLira, a fixed‐ratio combination therapy. (14th July 2015) - Kapitza, Christoph; Bode, Bruce; Ingwersen, Steen Hvass; Jacobsen, Lisbeth Vestergård; Poulsen, Pernille
Abstract: Insulin degludec/liraglutide (IDegLira) is a novel fixed‐ratio combination of the basal insulin insulin degludec (IDeg) and liraglutide, a glucagon‐like peptide‐1 analog. The pharmacokinetics (PK) and pharmacodynamics of IDegLira were assessed versus its components. A single‐dose, randomized, 4‐period crossover clinical pharmacology study in healthy subjects compared the bioavailability of IDegLira with its monocomponents. Dose proportionality, covariate effects on exposure, and exposure–response for change in glycated hemoglobin were analyzed based on data from a randomized treat‐to‐target phase 3 study in subjects with type 2 diabetes. Overall, the PK properties of IDeg and liraglutide were preserved for IDegLira. Liraglutide exposure was lower when dosed as IDegLira but met the criterion for equivalence. No relevant deviations from dose proportionality for the IDegLira components were observed. Covariate effects on exposure were consistent with previous results. Glycemic response to IDegLira was larger than with IDeg or liraglutide alone, reflecting their distinct glucose‐lowering effects throughout the dose/exposure range.